Improving Students’ Mathematical Problem-Solving Skill and Self-Efficacy through Problem-Based Learning Models with Scientific Approaches - Taufiqurrahman, Muhammad; Hidayat, Dayat (Journal of Mathematical Pedagogy (JoMP), 2022)
This study aims to determine (1) the mathematical problem-solving skills of students who receive the PBL model compared to students who receive conventional learning, (2) improving the mathematical problem-solving skills of students who receive the PBL model with a scientific approach compared to students who receive conventional learning, (3) self-efficacy of students who receive the PBL model with a scientific approach compared to students who receive conventional learning, (4) improving the self-efficacy of students who receive the PBL model with a scientific approach compared to students who receive conventional learning. The research method used was a quasi-experimental method with a population of all VIII grade students at one of the junior high schools in Cilegon. Sampling was carried out by cluster random sampling technique. This results showed that the mathematical problem-solving skill of students who received the PBL model with a scientific approach was better than students who received conventional learning,  improved problem-solving skills of students who get the PBL model with a scientific approach are better than students who get conventional learning,  the self-efficacy of students who receive the PBL model with a scientific approach is better than students who receive conventional learning, and the improving in self-efficacy of students who get the PBL model is better than students who get conventional learning. Based on the research results, learning the PBL model with a scientific approach can be an alternative learning to improve students' problem-solving skills and self-efficacy.